Community guidelines to increase the reusability of marine microfossil assemblage data - L. Jonkers; T. Strack; M. Alonso-Garcia; S. D'haenens; S. D'haenens; R. Huber; M. Kucera; I. Hernández-Almeida; C. L. C. Jones; B. Metcalfe; B. Metcalfe; R. Saraswat; et al. (Journal of Micropalaeontology)
Data on marine microfossil assemblage composition have multiple applications. Initially, they were primarily used for (chrono)stratigraphy and palaeoecology, but these data are now also widely used to study evolutionary and ecological processes, such as past biodiversity and its links with environmental dynamics, or to provide a basis for conservation efforts and biomonitoring. The large range of potential applications renders microfossil abundance data ideal for reuse. However, the complexity inherent in taxonomic data, which encompass extant and extinct species, coupled with the inherent intricacies of information on biological communities extracted from sedimentary archives, poses considerable hurdles in reusing marine microfossil data, even when they are publicly available. Here, we present guidelines derived from an online survey conducted within the marine micropalaeontological community, aimed at improving the reusability of microfossil assemblage data. These guidelines advocate for clarity and transparency in the documentation of the methods and the outcome, and we outline the data attributes required for effective reuse of micropalaeontological data. These guidelines are intended for researchers who generate microfossil abundance datasets and for reviewers, editors, and data curators at repositories.